2005
DOI: 10.1080/13548500512331315343
|View full text |Cite
|
Sign up to set email alerts
|

Psychological predictors of health-related behaviour in children

Abstract: Psychological variables such as self-efficacy, stress, and coping have proven their predictive power on health protective and health risk behaviour in adolescence and adulthood. Furthermore, health-related behaviour at early stages of development is seen as an important factor in determining health-related behaviour at later stages of development. Consequently, research on psychological variables predicting health-related behaviours at early stages of development should be an important topic with regard to hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
11

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 25 publications
1
10
0
11
Order By: Relevance
“…The program to cope with stress, personal development and relaxation led to a decrease in the children's state and trait anxiety mean scores showing that the children were learning to manage their stress effectively through education (Blankstein, Flett, & Watson, 1992;Klein-Hessling, 2005;Silvestri & Dantonio, 1996;Yurdabakan, 1999). These findings support our research results but are in contrast to those from studies by Omizo and Omizo (1992) in which no change was observed in anxiety level.…”
Section: State-trait Anxietysupporting
confidence: 85%
See 1 more Smart Citation
“…The program to cope with stress, personal development and relaxation led to a decrease in the children's state and trait anxiety mean scores showing that the children were learning to manage their stress effectively through education (Blankstein, Flett, & Watson, 1992;Klein-Hessling, 2005;Silvestri & Dantonio, 1996;Yurdabakan, 1999). These findings support our research results but are in contrast to those from studies by Omizo and Omizo (1992) in which no change was observed in anxiety level.…”
Section: State-trait Anxietysupporting
confidence: 85%
“…For this reason it is important to improve children's self-concept in order to improve their positive health behaviors. Klein-Hessling, Lohaus, and Ball (2005), however, determined that negative health behaviors have a negative effect on individual's self-efficacy and coping. Stress control programs conducted for the improvement of self-concept, personal development programs, programs for the improvement of self-esteem, and various reading programs have been shown to have a positive effect on individuals' self-perception (Chin, Finocchiora, & Rosenbrough, 1998;Guloglu, 1999;Henderson & Thomas, 1993).…”
Section: Self-conceptmentioning
confidence: 99%
“…Research also shows that risk behaviour is influenced by stress experiences that young people can't manage successfully with positive coping strategies (Klein-Hessling et al, 2005;Essau, 2004). Sexual intercourse at a young age is likely to be unplanned and therefore unprotected (Currie et al, 2004).…”
Section: Risky Behaviourmentioning
confidence: 96%
“…Research also shows that risk behaviour can be a response to stress experiences which young people cannot manage successfully (Klein-Hessling et al 2005).…”
Section: Risk and Safetymentioning
confidence: 98%